Reactive Oxygen Species in Cardiovascular Calcification: Role of Medicinal Plants - Qiao, Yu (Frontiers in Pharmacology, 2022)
Cardiovascular calcification, mainly including vascular calcification and calcific aortic valve disease (CAVD), is a serious worldwide health problem especially in older adults. The mechanisms underlying cardiovascular calcifications are complex and multifactorial. Increase in reactive oxygen species (ROS) and oxidative stress play important roles in the initiation and development of cardiovascular calcification. This mini review aims to summarize the recent evidence that support the association of ROS with vascular calcification and CAVD, discuss the role of medicinal plants for prevention and treatment of cardiovascular calcification.